Exercise therapy to prevent and treat Alzheimer’s disease - Pahlavani, Hamed Alizadeh (Frontiers in Aging Neuroscience, 2023)
Alzheimer’s disease (AD) is a progressive neurodegenerative disease in the elderly with dementia, memory loss, and severe cognitive impairment that imposes high medical costs on individuals. The causes of AD include increased deposition of amyloid beta (Aβ) and phosphorylated tau, age, mitochondrial defects, increased neuroinflammation, decreased synaptic connections, and decreased nerve growth factors (NGF). While in animals moderate-intensity exercise restores hippocampal and amygdala memory through increased levels of p-AKT, p-TrkB, and p-PKC and decreased levels of Aβ, tau phosphorylation, and amyloid precursor proteins (APP) in AD. Aerobic exercise (with an intensity of 50–75% of VO2 max) prevents hippocampal volume reduction, spatial memory reduction, and learning reduction through increasing synaptic flexibility. Exercise training induces the binding of brain-derived neurotrophic factor (BDNF) to TrkB and the binding of NGF to TrkA to induce cell survival and neuronal plasticity. After aerobic training and high-intensity interval training, the increase of VEGF, angiopoietin 1 and 2, NO, tPA, and HCAR1 in cerebral vessels causes increased blood flow and angiogenesis in the cerebellum, motor cortex, striatum, and hippocampus. In the hippocampus, exercise training decreases mitochondrial fragmentation, DRP1, and FIS1, improving OPA1, MFN1, MFN2, and mitochondrial morphology. In humans, acute exercise as an anti-inflammatory condition causes an acute increase in IL-6 and an increase in anti-inflammatory factors such as IL-1RA and IL-10. Moderate-intensity exercise also inhibits inflammatory markers such as IFN-γ, IL-1β, IL-6, CRP, TNF-α, sTNFR1, COX-2, and NF-κB. Aerobic exercise significantly increases plasma levels of BDNF, nerve growth factor, synaptic plasticity, motor activity, spatial memory, and exploratory behavior in AD subjects. Irisin is a myokine released from skeletal muscle during exercise and protects the hippocampus by suppressing Aβ accumulation and promoting hippocampal proliferation through STAT3 signaling. Therefore, combined exercise training such as aerobic training, strength training, balance and coordination training, and cognitive and social activities seems to provide important benefits for people with AD.